Community, conservation and climate-smart agriculture work hand in hand in northern Kenya - Nzuki, Esther Ndumi; Nderi, Alex Nduah; Gichunge Kathure, Karen; Ogutu, Elizabeth; Waswa, Boaz Shaban; Kasura, Stella (2025)
A strategic partnership between Lewa Wildlife Conservancy (LEWA) and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is driving the adoption of climate-smart agriculture (CSA) in northern Kenya. Through the Sustainable Agriculture Program, over 5,000 farmers have been trained in soil health, water conservation, and drought-tolerant crops, supported by demonstration farms and soil testing services. The initiative promotes inclusivity by engaging women, youth, and persons with disabilities, while agricultural expos strengthen market access and showcase bundled CSA technologies. Early results indicate improved crop yields, household incomes, and community resilience, demonstrating how science-based partnerships can scale CSA solutions and enhance food security and ecosystem conservation.